Public sopport for wind energy in Spain (2010)
This paper briefly attempts to describe and assess the legal and economicwind energy in Spain. We refer specifically to the system of public supportfor the production of electricity from renewables through the system called“premium.” The focus on wind energy in particular is justified simply for thereason that, as you know, Spain is ranked third worldwide in installed windpower second only to Germany and the U.S., which is coupled with the fact ofsignificance for all levels that has taken the wind power sector in our country.It should also be remembered that on the one hand, energy use (production andconsumption) is the main factor in emissions of greenhouse gases and on the otherhand, renewables are a key element in combating Climate Change. And also thatSpain is among the countries furthest away from compliance with the Kyoto Protocol. From this perspective, the role of wind energy is also evident in our countryin renewable energy, wind energy in particular is what is making the most ofelectricity generation mix, making it the most secure in this fight environmentaland global. In this sense, the proportion of electricity produced by wind-is over11% in 2008 - the second in the world, second only to Denmark. It is thereforeimportant to maintain a good policy to promote this renewable technology.